Effects of learning flow, learning interaction, and academic self-efficacy on learning satisfaction of college students who experienced HyFlex lecture - Kim, Sun-Ju (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the levels of learning flow, learning interaction, academic self-efficacy, and learning satisfaction among students who have experienced HyFlex lectures, as well as to investigate the correlations between these variables and the factors affecting learning satisfaction. The subjects of this study were 198 students taking HyFlex lectures offered in the first semester of 2024 who agreed to participate in the research among those attending a university located in Chungbuk. Data were collected through self-administered questionnaires from June 3 to June 10, 2024, using SPSS Statistics 22.0. The results of analyzing the differences according to general characteristics showed that learning satisfaction varied by type of class (F=4.728, p=.040) and was higher for theory classes compared to practical classes. It was also high when academic performance (F=11.089, p=.003) was ’above average.’ The factors affecting learning satisfaction were academic performance (β=.322, p<.01), learning flow (β=.377, p<.001), learning interaction (β=.395, p<.001), and academic self-efficacy (β=.297, p<.01). Learning interaction was the variable with the most significant positive effect on learning satisfaction. The results of this study can be used as foundational data for establishing improvement measures to enhance the quality of HyFlex lectures and the learning outcomes of learners.